Arthropathy-related pain in a patient with congenital impairment of pain sensation due to hereditary sensory and autonomic neuropathy type II with a rare mutation in the WNK1/HSN2 gene: a case report. Issue 1 (December 2016) - Yamada, Keiko; Yuan, Junhui; Mano, Tomoo; Takashima, Hiroshi; Shibata, Masahiko
Abstract Background Hereditary sensory and autonomic neuropathy (HSAN) type II withWNK1/HSN2 gene mutation is a rare disease characterized by early-onset demyelination sensory loss and skin ulceration. To the best of our knowledge, no cases of an autonomic disorder have been reported clearly in a patient withWNK/HSN2 gene mutation and only one case of a Japanese patient with theWNK/HSN2 gene mutation of HSAN type II was previously reported. Case presentation Here we describe a 54-year-old woman who had an early childhood onset of insensitivity to pain; superficial, vibration, and proprioception sensation disturbances; and several symptoms of autonomic failure (e.g., orthostatic hypotension, fluctuation in body temperature, and lack of urge to defecate). Genetic analyses revealed compound homozygous mutations in theWNK1/HSN2 gene (c.3237_3238insT; p.Asp1080fsX1). The patient demonstrated sensory loss in the "stocking and glove distribution" but could perceive visceral pain, such as menstrual or gastroenteritis pain. She experienced frequent fainting episodes. She had undergone exenteration of the left metatarsal because of metatarsal osteomyelitis at 18 years. Sural nerve biopsy revealed a severe loss of myelinated and unmyelinated nerves. She complained of severe pain in multiple joints, even on having pain impairment. Although non-steroidal anti-inflammatory drugs are generally more effective than acetaminophen for arthritis, in our case, they were ineffective and acetaminophen (2400 mg/day) adequately controlled her pain and improved quality of life. Over 3 months, the numerical rating scale, pain interference scale of the Brief Pain Inventory, and the Pain Catastrophizing Scale decreased from 6/10 to 3/10, from 52/70 to 20/70, and from 22/52 to 3/52 points, respectively. Conclusions This is the second reported case of a Japanese patient withWNK/HSN2 gene mutation of HSAN type II and the first reported case of an autonomic disorder in a patient with theWNK/HSN2 gene mutation. Acetaminophen adequately controlled arthropathy related pain in a patient with congenital impairment of pain sensation.